Counterterrorism and Human Rights: A Jurisprudential Critique - Muhammad Ateeq Ashraf; Sonia Aslam; Dr Muhammad Raees Ashraf; Dr Muhammad Ahsan Mukhtar, (Dialogue Social Science Review (DSSR), 2025)
Many people around the world now worry about how current security laws against terrorism respect basic human rights principles after September 11. This research analyzes the legal problems between human rights protection and counterterrorism rulemaking in several legal systems through modern interpretation of law. Our study employs doctrinal research to examine USA PATRIOT Act and UK Terrorism Acts plus Pakistan's ATA and PECA 2016 bytes and offers legal evaluations. It reviews important decisions made by both regional human rights bodies including ECtHR and supreme courts. This investigation examines established emergency power and derogation clause rules to determine their alignment with legal principles such as required standards and balanced regulations. Judicial systems worldwide show similar patterns of lowering fundamental rights protections as they let government control grow and accept these practices over time through terrorism countermeasures. The different judicial boards worldwide have distinct views on state power although some use a weighing approach while others approve extensive state control. This research shows that our public defense systems must be reformed so terrorist threats can be managed under constitutional security standards.